2006
DOI: 10.1016/j.pain.2005.12.001
|View full text |Cite
|
Sign up to set email alerts
|

Reduction of intractable deafferentation pain by navigation-guided repetitive transcranial magnetic stimulation of the primary motor cortex

Abstract: The precentral gyrus (M1) is a representative target for electrical stimulation therapy of pain. To date, few researchers have investigated whether pain relief is possible by stimulation of cortical areas other than M1. According to recent reports, repetitive transcranial magnetic stimulation (rTMS) can provide an effect similar to that of electrical stimulation. With this in mind, we therefore examined several cortical areas as stimulation targets using a navigation-guided rTMS and compared the effects of the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
134
0
12

Year Published

2010
2010
2018
2018

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 217 publications
(149 citation statements)
references
References 26 publications
2
134
0
12
Order By: Relevance
“…M1 is commonly targeted because stimulating M1 is believed to modulate lateral thalamic hyperactivity associated with sensory-discriminative information processing (Boggio et al, 2008;Lefaucheur et al, 2006;Tsubokawa et al, 1991aTsubokawa et al, ,b, 1993Yamashiro et al, 1994). Stimulation of other sensorimotor structures, such as the primary somatosensory cortex (S1), premotor, and supplementary motor area have failed to produce similar effects as M1 (Hirayama et al, 2006;Koyama et al, 1993). Although M1 is commonly targeted, benefits of M1 stimulation remain modest and variable (Lefaucheur et al, 2014), suggesting that networks other than the known sensory-discriminative components may be involved (Machado et al, 2013).…”
mentioning
confidence: 99%
“…M1 is commonly targeted because stimulating M1 is believed to modulate lateral thalamic hyperactivity associated with sensory-discriminative information processing (Boggio et al, 2008;Lefaucheur et al, 2006;Tsubokawa et al, 1991aTsubokawa et al, ,b, 1993Yamashiro et al, 1994). Stimulation of other sensorimotor structures, such as the primary somatosensory cortex (S1), premotor, and supplementary motor area have failed to produce similar effects as M1 (Hirayama et al, 2006;Koyama et al, 1993). Although M1 is commonly targeted, benefits of M1 stimulation remain modest and variable (Lefaucheur et al, 2014), suggesting that networks other than the known sensory-discriminative components may be involved (Machado et al, 2013).…”
mentioning
confidence: 99%
“…Electrical or magnetic stimulation of primary motor cortex has been associated with analgesia, leading to the suggestion that the primary motor cortex is an entry port for the modulation of pain processing circuits [31]. Animal work has shown that activation of Table 3.…”
Section: Discussionmentioning
confidence: 99%
“…It has also been regularly observed that, even in cases of bilateral or midline pain, stimulation on only one side of the brain is sufficient to modulate pain bilaterally [13]. Thus, Hirayama et al showed that relief of neuropathic pain was observed only when targeting M1, but not other areas [14]. Louppe et al [13] previously reported a beneficial analgesic effect of motor cortex stimulation with rTMS in two cases of noncancer pelvic pain [13].…”
Section: Introductionmentioning
confidence: 99%